STRATEGI DIGITAL MARKETING KAIN SONGKET PALEMBANG DALAM PENGEMBANGAN UMKM KAMPUNG KEMAS, SEBERANG ULU1 PALEMBANG - Pahalmas, Junior Zamrud; Pratiwi, Diany Putri; Havivi, Siti Lady; Widia, Putri; Rhamansyah, Rendy; Wagisri, Wagisri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2024)
This activity aims to develop digital marketing strategies and optimize applications on various digital platforms with the aim of building creative businesses as an effort to increase creative human resources and have competitive advantages in Palembang, even South Sumatra or even at the national level. This activity aims to identify the use of information and communication technology in building a creative economy with a digital marketing approach to increase the income of UMKM as a mode of economy for residents of Kampung Kemas, Kelurahan 2 Ulu, in Seberang Ulu 1 District, Palembang City. From the activities carried out, it can be obtained the results of activities in the field that Kampung Kemas which has various business units, there are good business opportunities in increasing household income and reducing poverty through the MSMEs that are run, it's just that there is still not enough education and motivation and innovation in the community so that it does not reach its maximum point in carrying out the technical use of digital marketing, namely online marketing communication and other social media advantages.